"I do not remember… You are reminding me now!": Children's difficult experiences during forensic interviews about online sexual solicitation. (December 2022) - Gemara, Netanel; Cohen, Noa; Katz, Carmit
Abstract: Background: Forensic interviews for children who have undergone online sexual solicitation (OSS) constitute a unique setting compared to other forms of child sexual abuse (CSA). In these cases, the interviewer holds concrete evidence of the abuse in the form of pictures or texts. During the interview, interviewers use these materials to advance the data collection regarding the abuse, a practice that may significantly influence the child's wellbeing. Objective: The current study aims to explore children's experiences during forensic interviews concerning OSS. Participants and setting: The sample included 20 Jewish children in Israel who were referred to and participated in a forensic investigation. Methods: A thematic qualitative methodology was used to analyze the children's narratives. Results: The findings demonstrate the children's difficulties when confronted with materials related to the abuse. The children detailed the different ways the interview challenged their wellbeing, including visualizing and verbalizing the abuse, new insights, and being videotaped. Conclusions: The findings in the current study emphasized the intrinsic challenges that children face in OSS forensic interviews resulting from the tension between the interviewer's need to collect details about the abuse and the child's desire to forget it. Practical ramifications pertaining to these threats to the child's wellbeing, future recommendations, and limitations of the study will be discussed.